Ultrastructural evaluation of the radioprotective effect of sodium selenite on submandibular glands in rats - Pontual,Maria Luiza dos Anjos (2007)
The aim of this study was to evaluate the radioprotector effect of sodium selenite on the ultrastructure of submandibular glands in rats. Fifty-seven male albino Wistar rats were randomized to 4 groups: control, irradiated, sodium selenite and irradiated/sodium selenite. The animals in the sodium selenite and irradiated/sodium selenite groups received intraperitoneal injections of sodium selenite (0.5 mg/kg body weight) 24 h before irradiation. The animals belonging to the irradiated and irradiated/sodium selenite groups were submitted to 15 Gy of gamma radiation in the head and neck region. The submandibular glands were removed at 4, 8, 12, 24, 48 and 72 h after irradiation. The ionizing radiation induced damage to the secretory cells, especially the serous cells, right from the first period. Vacuolization, lysis of cytoplasmic inclusions and nuclear alterations occurred. The sodium selenite group also presented cellular alterations in the study periods, but with less damage compared to that caused by radiation. There was greater similarity between the irradiated/sodium selenite group and the control group than with the other groups treated in all study periods. Despite the alterations observed in the sodium selenite group, sodium selenite presented a radioprotective action on the secretory cells of submandibular glands.